Technological Process of Recycling Melon and Police Products - Sharipov.S.Ya; Abdullayev Dilmurodjon Dilshodjon oʻgʻli; Urayimjonov Asrorjon Ahadjon oʻgʻli (Periodica Journal, 2023)
The expected result of the reforms is not only to collect and harvest the abundant harvest without losses, but also to organize its primary processing and increase the economic efficiency of this harvest. The newly created technology and technical means of melon drying and rind preparation are aimed at eliminating or to a certain extent reducing the above-mentioned shortcomings
Keywords: technology; productivity; melon